The trade-offs and synergies of the ecological-production-living functions of grassland in the Qilian mountains by ecological priority. (1st February 2023) - Liu, Youyan; Liu, Xingyuan; Zhao, Chuanyan; Wang, Hong; Zang, Fei
Abstract: Grassland degradation has caused increasingly prominent conflict between ecological environment conservation and socioeconomic development in the Qilian Mountains, China. How to effectively trade-offs and synergies to ecological and socioeconomic is essential to achieving the sustainable development of the grassland ecosystem. However, few studies have addressed the trade-offs and synergies of grassland ecosystem services in terms of coupling the natural ecosystem and the socioeconomic system. Therefore, we constructed an index of the analyzed trade-offs and synergies of grassland ecosystem services from the perspective of "ecological-production-living" functions (EPLFs) and analyzed the spatial-temporal characteristics of grassland EPLF trade-off and synergy relationships based on the data from the implementation of three conservation policies in the Qilian Mountains from 2003 to 2020. The results showed evident spatial and temporal differentiation of the grassland EPLFs. The ecological function was consistent with the production function, trending upward initially and then decreasing. The living function showed a trend of continuous increase. The spatial pattern of grassland EPLFs showed that the northwest and southeast were more active than the middle of the Qilian Mountains, and the regional gradient difference was apparent. The trade-off and synergy relationships of grassland EPLFs have obvious spatial correlations as well; spatial differences were evident under different conservation policies. With national park construction, the synergistic relationship gradually weakened and the trade-off relationship gradually strengthened. These results suggest that the policy of ecological priority increased trade-offs and reduced synergies among EPLFs was not conducive to coupling and coordinating grassland EPLFs for development in the Qilian Mountains. Our study also demonstrates that maintaining moderate grassland grazing pressure and the appropriate number of herdsmen is crucial to sustainably develop the grassland ecosystem in the Qilian Mountains, and further research into coupling mechanisms for grassland EPLFs is needed to reduce trade-offs and increase synergies with grassland ecosystem services. Graphical abstract: Image 1 Highlights: The trade-off/synergy index system of grassland was constructed from EPLFs. The spatio-temporal characteristics of EPLFs of trade-offs/synergies were analyzed. Trade-off was the dominant relationship type between grassland EPLFs. Excessive emphasis on grassland protection has limit development.